Acquired Inhibitors of Factor V - Feinstein, Donald I (Thrombosis and Haemostasis, 1978)
The clinical and laboratory data on the 12 patients with an acquired inhibitor to factor V have been reviewed. The degree of clinical bleeding in these patients varied from none to severe, and in most patients the inhibitor was transient. The combination of a markedly prolonged partial thromboplastin time and Quick prothrombin time and failure of normal plasma to correct these tests, in the presence of a normal thrombin and prothrombin and proconvertin time, seems to be pathognomonic for a factor V inhibitor. The inhibitors have physicochemical properties of immunoglobulins and a few have been characterized as polyclonal IgG antibodies or a mixture of IgM and IgG antibodies. The etiology and pathophysiologic mechanism of their development is unknown, but there seems to be a close relationship to major surgery. When tested with inhibitor plasma, the plasmas from 9 patients with hereditary factor V deficiency from 7 unrelated families did not contain factor V antibody-neutralizing material.